2020
DOI: 10.1007/s00259-020-04707-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of FDG-PET/CT in children with fever of unknown origin

Abstract: Purpose To determine the role of 18F-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET)/computed tomography (CT) in children with fever of unknown origin (FUO). Methods This retrospective single-center study included 110 children (0–18 years) with FUO who underwent FDG-PET/CT between 2010 and 2019. The diagnostic value of FDG-PET/CT for identifying cause of fever was calculated, treatment modifications after FDG-PET/CT were assessed, and logistic regression analyses were performed to identify cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Elevated CRP level correlated with a positive FDG-PET/CT finding, although low CRP did not preclude positive findings. In a large cohort of children with FUO, Pijl et al also found that CRP level was positively associated with true positive FDG-PET/CT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated CRP level correlated with a positive FDG-PET/CT finding, although low CRP did not preclude positive findings. In a large cohort of children with FUO, Pijl et al also found that CRP level was positively associated with true positive FDG-PET/CT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, 47 scans were performed on stand-alone PET scanners without CT (with 40% helpful scans versus 53% helpful scans in PET scans with CT). A recent study including the largest cohort of pediatric patients with FUO thus far ( n = 110) reported that in 68/110 (62%) patients, a definite cause of fever was identified, where in 53 of 68 (78%), this cause was detected by FDG-PET/CT (53 of a total of 110 scans, 48%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) imaging demonstrates increased uptake across a variety of pathological etiologies including infections, inflammatory processes, and neoplasms. For example, FDG PET-CT imaging has been demonstrated to be useful in localizing foci of infection and inflammation in patients with fever of unknown origin [13]. In cases of COVID-19 infection documented on whole-body PET/CT, interstitial pneumonia is the predominant imaging manifestation, with multifocal bibasilar predominant ground glass opacities demonstrating increased FDG uptake in the lung parenchyma [14][15].…”
Section: Introductionmentioning
confidence: 99%